2020
DOI: 10.3390/math8040633
|View full text |Cite
|
Sign up to set email alerts
|

Deep Assessment Methodology Using Fractional Calculus on Mathematical Modeling and Prediction of Gross Domestic Product per Capita of Countries

Abstract: In this study, a new approach for time series modeling and prediction, “deep assessment methodology,” is proposed and the performance is reported on modeling and prediction for upcoming years of Gross Domestic Product (GDP) per capita. The proposed methodology expresses a function with the finite summation of its previous values and derivatives combining fractional calculus and the Least Square Method to find unknown coefficients. The dataset of GDP per capita used in this study includes nine countries (Brazil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The main motivation is to model the given discrete dataset and obtained a continuous curve representing the dataset with the minimum error. To achieve this goal, the Taylor expansion is employed at the first stage of the mathematical manipulations [18][19][20][21].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The main motivation is to model the given discrete dataset and obtained a continuous curve representing the dataset with the minimum error. To achieve this goal, the Taylor expansion is employed at the first stage of the mathematical manipulations [18][19][20][21].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…(𝜖 𝑖 ) 2 = (𝑝 𝑖 − 𝑓(𝑥 𝑖 )) 2 (10) The total square of the error is defined as Equation ( 11) and according to the least-squares method, the sum of error squares 𝜖 𝑇 2 is tried to be minimized [18][19][20].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of the small squares and its modifications is often applied for macroeconomic modelling of GDP dynamics, with the help of which the coefficients of the regression function reflecting the dynamics of the indicator are estimated. The group of researchers (Karaçuha et al, 2020) used the small squares method to forecast GDP per capita for the population of Brazil, China, India, Italy, Japan, the UK, the USA, Spain and Turkey. It has been shown that their proposed method is superior to the polinomial and fractional models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In financial mathematics, FC is employed in price volatility modeling. Furthermore, Symmetric properties contribute to numerous applications that depend on TSFDEs, such as applications of physics, chemistry, and engineering, so these properties play an important role in knowing the correct way to solve these equations [1,2]. In physics, long particle jumps in anomalous diffusion and the particle motions in a heterogeneous environment were modeled with the help of it.…”
Section: Introductionmentioning
confidence: 99%